Progressive Lefts versus Far-Rights: Socioeconomic and Political Reflections with Education as a Solution - Copertari, Luis F.; Reyna, Gloria V. (Advances in Social Sciences Research Journal, 2025)
The clash between progressive lefts and the far right is a global phenomenon that impacts socioeconomic and political spheres. Progressive lefts seek a just and egalitarian society with an active state in wealth redistribution, while the far right defends traditional values, a strong state, and nationalist policies. This ideological conflict manifests in political polarization and the erosion of trust in institutions. Education is presented as a crucial tool to foster critical thinking, tolerance, and citizen participation, contributing to the construction of a more just and equitable future.